2012
DOI: 10.1080/09613218.2012.698069
|View full text |Cite
|
Sign up to set email alerts
|

Resilience to increasing temperatures: residential building stock adaptation through codes and standards

Abstract: The resilience of the current Spanish residential building stock to increased temperatures is modeled. Homogenised daily temperature data recorded at 50 Spanish meteorological stations for the periods 1950 -1979 and 1981 -2010 were used to investigate anticipated climate warming on Spanish residential building stock by means of the degree day method. Impacts on residential buildings were investigated for three different future time periods (2011-2040, 2041-2070 and 2071-2100) for three representative Spanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…According to Gangolells et al, [69], 59% of the current Spanish residential building stock was erected before the first thermal regulation NBE-CT-79 [70]. Nearly 38% of Spanish residential buildings already in use were built under NBE-CT-79 [70], satisfying the minimum thermal requirements.…”
Section: Case Studiesmentioning
confidence: 99%
“…According to Gangolells et al, [69], 59% of the current Spanish residential building stock was erected before the first thermal regulation NBE-CT-79 [70]. Nearly 38% of Spanish residential buildings already in use were built under NBE-CT-79 [70], satisfying the minimum thermal requirements.…”
Section: Case Studiesmentioning
confidence: 99%
“…National Adaptation Plans are generally considered the backbone of regulation and strategies regarding adaptation, although approaches for implementing and evaluating the proposed strategies seem to be lacking [19]. This gap is acknowledged by Gangolells et al [20] while exploring the impacts of the Spanish stock of buildings to climate and summer overheating. It argues for the role of regulatory instruments, until now focusing strongly on mitigation, as well as the very constitution of the existing building stock, concerning age and physical quality.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, Southern Europe is characterized by a stable and aging building stock of significant proportions, mainly built prior to the implementation of thermal regulations [6], which has been already been identified as a major challenge regarding sustainable development [21]. In existing buildings, adequate thermal performance is mainly promoted through retrofitting actions, prone to increase thermal insulation and air-tightness, and several authors have already suggested that a heating-reduction driven policy and decision-making regarding measures such as insulation, can have unexpected effects if considered in a climate change context [22,13,20]. These studies also stress the fact that most literature dedicated to adaptation regarding thermal comfort is technically focused and driven to understand adaptation measures to be applied to buildings [12,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Offices built before 1981 have no thermal protection, as the first legislation regulating buildings' thermal conditions, NBE-CT 79 [49], was introduced in Spain in 1979. This prescriptive code was in force from 1981 to 2006 and set minimum thermal requirements for individual building envelopes by establishing maximum heat transmission coefficients, and a maximum overall heat transmission coefficient for the entire building [50]. Thermal requirements were overhauled in 2007, when the Spanish Technical Building Code was introduced [51].…”
Section: Construction Periodmentioning
confidence: 99%